Digital Integration in Higher Education: A Survey Research in Nepal - Dahal, Santiram (Journal of Janta Multiple Campus, 2025)
This article explores challenges and opportunities of digital integration in Nepalese higher education Survey method is used to conduct research. An online survey is designed and disseminated through what’s app group of teachers of various institutions. This study is based on 170 responses. Digital integration is valued by all 170 respondents, yet the digital gap and a lack of skilled teachers remain. The study identifies barriers and proposes solutions to improve digital tool uptake and use in teaching and learning to inform policymakers and educators. " Despite this, the digital gap, unequal technology access, and a shortage of technology-based learning teachers remain. The necessity for professional growth was highlighted by 64.7% of respondents requesting digital training. The fact that 64.7% have access to quality e-resources while 35.3% do not highlights inequities that must be addressed. Digital tool use varies, with 35.3% always and 35.3% sometimes. Digital skills improve classroom interaction and teamwork, with 82.4% perceiving an increase. However, digital gap and technology overuse remain challenges. These findings highlight the need for comprehensive measures to improve digital literacy, infrastructure, and equitable access to maximize digital education in Nepal and prepare students for the digital age. Recommendations are provided to inform policy makers and educators to enhance digital literacy and maximizing the benefits of digital education in Nepal.